INTEGRATING ACTIVE TEACHING METHODS INTO THE DEVELOPMENT OF PROFESSIONAL SKILLS IN ENVIRONMENTAL ENGINEERING STUDENTS (PANGEEA, 2026)
ABSTRACT: This paper analyzes the importance of active teaching methods in higher education, with a focus on the field of Environmental Engineering. Emphasis is placed on the correlation between modern teaching strategies and the development of essential professional skills for future environmental engineers. Models for integrating participatory methods, such as project-based learning, problem-based learning, and case studies, into specific disciplines are proposed. The study includes an analysis of their effectiveness in relation to traditional methods, based on the literature and practical examples.